Myaesthenia gravis exacerbation caused by axillary injection of botulinum toxin A for treatment of hyperhidrosis. (1st April 2017) - El‐Heis, S.; Burke, G.; Gibb, W.; Ardern‐Jones, M. R.
Abstract: Click here for the corresponding questions to this CME article.